Delivery Platforms for CRISPR/Cas9 Genome Editing of Glial Cells in the Central Nervous System - Meneghini, Vasco; Peviani, Marco; Luciani, Marco; Zambonini, Giada; Gritti, Angela (Frontiers in Genome Editing, 2021)
Glial cells (astrocytes, oligodendrocytes and microglia) are emerging as key players in several physiological and pathological processes of the central nervous system (CNS). Astrocytes and oligodendrocytes are not only supportive cells that release trophic factors or regulate energy metabolism, but they also actively modulate critical neuronal processes and functions in the tripartite synapse. Microglia are defined as CNS-resident cells that provide immune surveillance; however, they also actively contribute to shaping the neuronal microenvironment by scavenging cell debris or regulating synaptogenesis and pruning. Given the many interconnected processes coordinated by glial cells, it is not surprising that both acute and chronic CNS insults not only cause neuronal damage but also trigger complex multifaceted responses, including neuroinflammation, which can critically contribute to the disease progression and worsening of symptoms in several neurodegenerative diseases. Overall, this makes glial cells excellent candidates for targeted therapies to treat CNS disorders. In recent years, the application of gene editing technologies have redefined therapeutic strategies to treat genetic and age-related neurological diseases. In this review, we discuss the advantages and limitations of CRISPR/Cas9-based gene editing in the treatment of neurodegenerative disorders, focusing on the development of viral- and nanoparticle-based delivery methods for in vivo glial cell targeting.